Delayed 18F-FDG PET imaging provides better metabolic asymmetry in potential epileptogenic zone in temporal lobe epilepsy - Hong, Yang; Fu, Chang; Xing, Yazhou; Tao, James; Zhao, Ting; Wang, Na; Chen, Yanan; You, Yang; Ren, Zhe; Hong, Yingxing; Wang, Qi; Zhao, Yibo; et al. (Frontiers in Medicine, 2023)
Objective To investigate the value of 18F-FDG positron emission tomography/computed tomography (PET/CT) two time point imaging for the identification of the potential epileptogenic zone (EZ) in temporal lobe epilepsy (TLE). Methods Fifty-two patients with TLE were prospectively enrolled in the 18F-FDG PET/CT two time point imaging study. The early imaging was obtained approximately 40 min (43.44 ± 18.04 min) after 18F-FDG injection, and the delayed imaging was obtained about 2 to 3 h (160.46 ± 28.70 min) after the injection. Visual and semi-quantitative analysis of 18F-FDG uptake were performed at the two time points in EZ and contralateral symmetrical region. The mean standardized uptake value (SUVmean) of EZ and contralateral symmetrical region was calculated to determine the asymmetry index (AI) of the early and delayed images, as well as in the MRI positive and negative patient groups. Results Semi-quantitative analysis demonstrated that AI of the early and delayed 18F-FDG PET/CT images was 13.47 ± 6.10 and 16.43 ± 6.66, respectively. The ΔAI was 2.95 ± 3.05 in 52 TLE patients between the two time points. The AI of the EZ was significantly elevated in delayed images compared to the early images (p < 0.001). The AI of delayed imaging was also significantly elevated compared to the early imaging in both MRI positive (ΔAI = 2.81 ± 2.54, p < 0.001) and MRI negative (ΔAI = 3.21 ± 3.91, p < 0.003) groups, and more pronounced in MRI negative group. Visual analysis also showed that the delayed imaging appeared to be superior to the early imaging for identification of potential EZ. Conclusion Delayed 18F-FDG PET imaging provided significantly better than the early imaging in the identification of potential EZ, which can be valuable during epilepsy pre-surgical evaluation in patients with TLE.